Efficient way of implementing the random and GM (Gauss-Markov) mobility model in MANET - Nagaraju, M; Raghava Rao, K; Vijayalakshmi, K (International Journal of Engineering and Technology, 2018)
In Mobile Adhoc Network (MANET) nodes are communicating each other with the help of routing protocol. In Adhoc networks, a node having high mobility, with that node’s moving randomly from node to node. For observing the movement mobility, we are studying different forms of mobility. These models can deploy the mobility of the network condition, including the various parameters such as the size of the network, traffic models of data, throughput and the PDR (Packet Delivery Ratio) are used as performance Parameters. We are investigating the RWP (Random Waypoint) and GM (Gauss-Markov) mobility model to express efficiency of Adhoc routing protocol by using the OMNET++ simulator .The result of the simulator shows that the mobility has more influence upon MANET protocol with the increasing node density. Here, we evaluated RWP and GM mobility model with AODV protocol. The study of these models illustrates dissimilar outcomes related inputs with the increasing performance of the pause time rises among the speed and number of nodes.